A Depth‐Transect of Ocean Deoxygenation During the Paleocene‐Eocene Thermal Maximum: Magnetofossils in Sediment Cores From the Southeast Atlantic. Issue 8 (14th August 2022) - Xue, Pengfei; Chang, Liao; Dickens, Gerald R.; Thomas, Ellen
Abstract: The Paleocene‐Eocene Thermal Maximum (PETM, ∼56 Ma) presents a past analog for future global warming. Previous studies provided evidence for major loss of dissolved oxygen during the PETM, although understanding the degree and distribution of oxygen loss poses challenges. Magnetofossils produced by magnetotactic bacteria are sensitive to redox conditions in sediments and water columns, and have been used to reconstruct paleoredox conditions over a range of geological settings. Here, we present records of well‐preserved magnetofossils from cores along Walvis Ridge in the Southeast Atlantic that span the PETM across a depth transect (∼1, 500–3, 600 m paleodepth). Hysteresis, isothermal remanent magnetization curves, first‐order reversal curve diagrams, and low‐temperature magnetic measurements document large variations in magnetic properties of magnetofossils, which relate to time and water depth. Abundant magnetofossil grains are present within the studied sediments, and their morphologies change with paleodepth, as shown by transmission electron microscope observations. Magnetofossils from samples within the PETM onset at the deeper sites (∼2, 600–3, 600 m paleodepth) have lower coercivity values, a higher oxidation degree, and smaller grain sizes than those from shallower sites (∼1, 500–1, 800 m paleodepth), likely reflecting changes in paleoredox conditions at different paleodepths. We use the magnetofossil records to reconstruct relative changes in dissolved oxygen content at different water depths through the PETM, and suggest that ocean deoxygenation likely expanded downwards in the early stages of the PETM. We thus demonstrate the value of magnetofossil records for paleoenvironmental reconstructions over time and space, particularly for sediments that lack carbonate fossils. Plain Language Summary: The Paleocene‐Eocene Thermal Maximum (PETM, ∼56 Ma) was the most severe global warming event over at least the last 65 million years. Understanding environmental perturbations across this interval can provide insights into our current and future warming world. Magnetofossils may be preserved in sediments after the death of magnetotactic bacteria or other microorganisms, and may record critical paleoenvironmental information, including on marine productivity and oxygenation. Here, we use a newly proposed magnetofossil‐based proxy to reconstruct ocean oxygenation along a water depth transect (∼1, 500–3, 600 m) spanning the PETM in the Southeast Atlantic (Walvis Ridge). Our paleoenvironmental reconstructions indicate that deoxygenated seawater expanded downwards during the early warming stages of the PETM, and demonstrate the use of magnetofossils as paleoredox proxies. Key Points: Large variations in magnetofossil signatures at different South Atlantic paleodepths during the Paleocene‐Eocene Thermal Maximum (PETM) Magnetic properties combined with morphological data of magnetofossils trace paleoredox changes at different water depths during the PETM Magnetofossil records suggest lowered ocean oxygenation during the PETM in intermediate and deep waters